Histological and biochemical investigation of the renoprotective effects of metformin in diabetic and prostate cancer model. (2nd September 2021) - Koroglu-Aydın, Pınar; Bayrak, Bertan Boran; Bugan, Ilknur; Karabulut-Bulan, Omur; Yanardag, Refiye
Abstract: Background: Diabetes and cancer have common physiological and biochemical mechanisms. Metformin is the preferred drug of choice for the treatment of diabetes. Prostate cancer can be modeled in by injection of MAT-Lylu cells. A model of diabetes in rats is induced by streptozotocin injectıon. In the current study, we explored the mechanisms by which diabetes accelerates cancer, and evaluated the effects of metformin to know whether it has any impact against the damage caused by cancer and diabetic + cancer via histopathological and biochemical parameters of kidney tissue. Methods: The experiment was carried out in rats. Groups 1-Control, 2- Diabetic, 3-Cancer, 4-Diabetic + cancer, 5-Diabetic + cancer + metformin, 6-Cancer + metformin. Metformin treatment was applied by gavage every day. The research ended on the 14th day. The collected kidney tissue sections were stained with Hematoxylin-Eosin. Results: Histological evaluation showed moderate to severe damage to the kidney tissue following diabetic and cancer processess. In diabetic, cancer and diabetic + cancer groups, reduced glutathione levels, total antioxidant status, sodium/potassium-ATPase and paraoxonase1 activities were found to be significantly abated. While advanced oxidized protein products, lipid peroxidation, nitric oxide, tumor necrosis factor-alpha, reactive oxygen species levels, total oxidant status, catalase, superoxide dismutase, glutathione-related antioxidant enzymes, myeloperoxidase, and arginase activities were significantly raised. The administration of metformin reversed these defects. The outcome of the reveals that histopathological and biochemical damage in cancer and diabetes + cancer groups decreased in the groups that received metformin. Conclusion: In conclusion, metformin treatment can be considered an adjuvant candidate for kidney tissue in diabetes, prostate cancer and cancer therapy related damage.